Benchmarking assessment of development options for low-capacity centralized heating systems - Dryomin V.P.; Dryomin I.V.; Shafranovich Ju.V.; Silenko N.F. (General Energy Institute of the National Academy of Sciences of Ukraine, 2015)
A set of quantitative characteristics of centralized heat supply (DH) systems is proposed, which makes it possible to assess the effectiveness of the implementation of various options for target programs for the development of these systems. The efficiency of the district heating system is assessed on the basis of indicators of controllability, development and operational indicators in accordance with the criteria: deadlines, design degree of centralization of the heat supply system, reliability of its operation and financial costs in the operational phase.